Urgensi Kinerja Kepala Sekolah dalam Peningkatan Pendidikan Karakter Islam dan Budi Pekerti di SMAN 2 Semarang - Eneng Muslihah; Anis Fauzi; Muhammad Rifdillah; Wawan Gunawan; Farid Ma’ruf (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the influence of the principal's performance in implementing character and morals education at SMAN 2 Semarang and to determine the implementation of character and morals education at SMAN 2 Semarang. This research uses a qualitative approach with phenomenological methods. This research was carried out at SMAN 2 Semarang. The research subjects consisted of the Principal, Teacher Council, and students. Data collection techniques include observation, interviews, and documentation, and data analysis techniques using the interactive model from Miles and Huberman, where the analysis process is carried out simultaneously with the observation and interview process, and documentation is directly analyzed. As a result of the research, it is essential to know how character and ethical education are implemented and how the principal's performance influences the implementation of Islamic character and moral education at SMAN 2 Semarang. The conclusion is that the school principal's performance significantly affects the education of Islamic character and manners. Keywords: Character, Character Education, Principal Performance.